1987
DOI: 10.1210/endo-121-6-2075
|View full text |Cite
|
Sign up to set email alerts
|

The Trafficking and Processing of Insulin and Insulin Receptors in Cultured Rat Hepatocytes*

Abstract: The processing and trafficking of insulin in cultured rat hepatocytes were studied. A time course of binding of radiolabeled insulin to hepatocytes at 37 C revealed a rapid rise in cell-associated radioactivity that reached a steady state by 20 min. Using an acid medium to extract insulin bound to surface receptors, the time courses of receptor binding and internalization of the ligand were characterized. The earliest event in insulin processing was the binding of insulin to surface receptors, reaching steady … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1

Year Published

1989
1989
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 44 publications
2
38
1
Order By: Relevance
“…Intracellular insulin degradation will change free insulin concentration in lymph, which in turn may influence diffusion across the capillary wall. Lymph insulin levels may also be altered by retroendocytosis (54,55), a process by which internalized intact hormone is recycled to the plasma membrane and extruded into the interstitial space; however the quantitative importance of this reverse process in vivo is unclear. Lastly, one must be cautious of the use of inulin as a reference molecule for transcapillary insulin diffusion.…”
Section: Resultsmentioning
confidence: 99%
“…Intracellular insulin degradation will change free insulin concentration in lymph, which in turn may influence diffusion across the capillary wall. Lymph insulin levels may also be altered by retroendocytosis (54,55), a process by which internalized intact hormone is recycled to the plasma membrane and extruded into the interstitial space; however the quantitative importance of this reverse process in vivo is unclear. Lastly, one must be cautious of the use of inulin as a reference molecule for transcapillary insulin diffusion.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, maximal insulin binding by hepatocytes coincides with the insulin concentration range present in the insulin concentration wavefront within a pulse presented to the liver in the portal vein, ϳ1,000 -4,000 pmol/l. In contrast, hepatocyte insulin binding is much less avid at insulin concentrations typically present in the trough of an insulin pulse train, which represents a basal nonpulsatile component of release (32)(33)(34). High binding in insulin pulses would be expected to result in endocytosis of a high proportion of insulin delivered to the hepatic sinusoids.…”
Section: Discussionmentioning
confidence: 99%
“…Written informed consent was obtained from all study participants. Five healthy subjects (two men and three women) mean age 32 years (range [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39], with a mean BMI of 24.9 kg/m 2 (21.2-27.1) participated. All subjects were nondiabetic based on fasting plasma glucose concentration (mean fasting plasma glucose 5.4 mmol/l [5.1-5.8]) and HbA 1c values (mean 4.8% [4.5-5.0]).…”
Section: Methodsmentioning
confidence: 99%
“…Screening with a multivalent nonapeptide phage display library has revealed that ten of thirteen EH domains from (Tang and Cai, 1996;Di Fiore et al, 1997;Haner et al, 1997;Tang et al, 1997;Wendland and Emr, 1998). Similar to many cell surface receptors, the insulin receptor is internalized into intracellular vesicular compartments following ligand binding and tyrosine kinase activation (Levy and Olefsky, 1987;Backer et al, 1989). It has been shown that insulin receptor kinase tyrosine autophosphorylation in conjugation with the dileucine motifs located in juxtamembrane domain of the bsubunit is essential for the insulin receptor internalization (Backer et al, 1992;Hamer et al, 1997) and that the insulin receptor internalization occurs through a dynamin-and clathrin-mediated endocytic pathway (Ceresa et al, 1998).…”
Section: Discussionmentioning
confidence: 99%